Effect of design parameters and operational conditions on the motion accuracy of hydrostatic thrust bearing. (April 2020) - Zha, Jun; Chen, Yaolong; Zhang, Penghai; Chen, Runlin
In this study, the effect of design parameters and operational conditions on motion accuracy of the closed configuration hydrostatic thrust bearing was researched. Key design parameters include land width, nominal oil film thickness, and perpendicularity error between mandrel and thrust plates. Oil supply pressure, external load, and rotation load are the considered operational conditions. Predictions of the induced effect are made by introducing oil film clearance function, governing equations, flow rate continuity equations, and dynamic equations of mandrel to model axial rotation error and angular motion error. The results show that the axial rotation accuracy increased, as land width (larger than 8 mm), nominal oil film thickness, and oil supply pressure increased, but there was little impact on angular motion error. The axial rotation error and angular motion error increased with the increase in the external load and rotation speed. Confirmation of the perpendicularity error has been achieved, in this study, by conducting experiments, using ultra-precision measuring machine. In addition, axial rotation error was tested on a hydrostatic rotary table and compared with the simulation results to check the validity of the proposed method. The results provide useful design guidelines and operation advice for hydrostatic thrust bearing in high-precision machine tools.